Terpenoids from Microliabum polymnioides - Díaz, Oscar J. (2004)
The phytochemical study of M. polymnioides led to the isolation of two sesquiterpene lactones namely: 11aH-dihydrozaluzanin E and 1b-hydroxy-4-oxo-11bH-4-noreudesman-6,12-olide. Their structures were determined by spectroscopic methods. The relative stereochemistry was established by a combination of coupling constant analysis, NOESY correlations and molecular modeling. Three related known sesquiterpene lactones were also identified, and these data were used for chemotaxonomical purposes.